INTERNALIZING DISCIPLINE CHARACTER TO SENIOR HIGH SCHOOLS STUDENTS - Hasan, Nurangsih S; Suabuana, Cik; Warlim, Warlim (Balai Diklat Keagamaan Bandung, 2023)
The internalization of discipline is a necessary character value to follow the many regulations of a school. Students at SMA Negeri 1 Halmahera and SMA Negeri 7 in the South Halmahera Regency were surveyed for this study with the hope of encouraging them to adopt a more disciplined mindset. Qualitative research techniques were used for this analysis. Using an approach based on habituation of disciplinary values, experience, and exercises to strengthen discipline values, and exemplary application by exemplary teachers and students as role models. The results showed that SMA Negeri 1 and SMA Negeri 7 in South Halmahera Regency, North Maluku Province successfully internalized disciplinary values. Students who 1) arrive at school promptly at 7.00 WIT; 2) read a short letter for 15 minutes before beginning the lesson; and 3) stay for 5 minutes after the end of class to sing the national anthem are more likely to internalize the discipline. These three activities are performed daily. The cultivation of discipline in students, particularly through adherence to established norms and programs, enables them to effectively incorporate these principles into their daily lives. Keywords: values internalization; character; students’ discipline; senior high school